Pengaruh Independensi Auditor Terhadap Integritas Laporan Keuangan (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2013-2015)” - F Fitrawansyah; Maulidia Syahnifah (Department of Accounting-Faculty of Economic and Business (FEB), 2018)
In this study studied is the influence of auditor independence on the integrity of financial statements at manufacturing companies listed on the Indonesia Stock Exchange (BEI). In this research use secondary data. The sample of this research is manufacturing company year 2013-2015 by using purposive sampling method. There are 41 companies that meet the criteria as the research sample. This research uses descriptive research with quantitative method. Result of hypothesis test of partial correlation states that variable of auditor independence (X) has no effect to integrity of financial statement (Y) where sig value. (2-tailed) of 0.115 and the probability significance of 0.206> 0.05. While the results of testing the significance of a simple correlation obtained value of auditor independence variable significance of 0.693 value above the level of significance that has been specified that is 0.05. From this research only test one variable that allegedly have an effect on to integrity of financial statement, so that only can explain its influence equal to 0,5%, and the rest influenced by other variable not examined in this research.